Răspuns :
d)5(x^2-1)=5(x-1)(x+1)
e)12a(x^2-1)=12a(x-1)(x+1)
f)3x(x^2-4)=3x(x-2)(x+2)
g)4x^2(x^2-4)=4x^2(x-2)(x+2)=(2x)^2(x-2)(x+2)
h)5x(x^2-9)=5x(x-3)(x+3)
i)(x^2-6x)(x^2+6x)
j)2x^2(x^2-4)=2x^2(x-2)(x+2)
k)7x(x^2-4)=7x(x-2)(x+2)
l)x(x^4-16)=x(x^2-4)(x^2+4)=
x(x-2)(x+2)(x^2+4)
e)12a(x^2-1)=12a(x-1)(x+1)
f)3x(x^2-4)=3x(x-2)(x+2)
g)4x^2(x^2-4)=4x^2(x-2)(x+2)=(2x)^2(x-2)(x+2)
h)5x(x^2-9)=5x(x-3)(x+3)
i)(x^2-6x)(x^2+6x)
j)2x^2(x^2-4)=2x^2(x-2)(x+2)
k)7x(x^2-4)=7x(x-2)(x+2)
l)x(x^4-16)=x(x^2-4)(x^2+4)=
x(x-2)(x+2)(x^2+4)